Patient with Antineutrophil Cytoplasmic Antibody Associated Small Vessel Vasculitis, Acute Renal Failure, and Coronavirus Disease-19 Pneumonia: A Diagnostic and Therapeutic Challenge - Gerasimovska-Kitanovska, Biljana; Selim, Gjulshen; Petronijevik, Zvezdana; Pecanova, Blagica; Stojchev, Gjorgi; Eftimovska-Otovic, Natasha; Zdravevska, Marija; Jovanovska-Janeva, Elena; Antova, Dubravka; Curakova, Elena (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Antineutrophil cytoplasmatic antibody (ANCA)-associated vasculitis (AAV) has a predilection for the kidney and more than three quarters of patients have renal involvement with rapidly progressive glomerulonephritis. Small-vessel systemic vasculitis may present as pulmonary-renal syndrome and is characterized by necrotizing glomerulonephritis and pulmonary hemorrhage. Diagnosis and therapy for AAV in coronavirus disease (COVID) COVID-19 pandemic require multi-disciplinary collaboration due to the affection of multiple systems and risks associated with immunosuppressive medications. CASE REPORT: A 69-year-old non-smoker, non-diabetic female presented in the outpatient unit at the department of pulmonology with dry cough, malaise, and sub-febrile temperature, lasting for 1 month. The patient had a high suspicion of severe pulmonary-renal syndrome, ANCA-AAV, and acute renal failure requiring hemodialysis. She was treated with corticosteroids, cyclophosphamide, and plasma exchange. The treatment led to temporary improvement. Infections with COVID-19, Enterococcus in the urine, and Acinetobacter in the tracheal aspirate further complicated the clinical picture and despite antibiotic treatment, use of tocilizumab and convalescent plasma, the outcome was lethal. CONCLUSION: It is important to establish the diagnosis and distinguish accurately between vasculitis and infection to provide adequate and timely therapy.